Use of Health Professionals for Delivery Following the Availability of Free Obstetric Care in Northern Ghana - Mills, S.; Williams, J. E.; Adjuik, M.; Hodgson, A. (2012)
OBJECTIVES: To assess the factors associated with the use of health professionals for delivery following the implementation of a free obstetric care policy in the poorest regions of Ghana. METHODS: All 4,070 women identified in the Navrongo demographic surveillance system with pregnancy outcomes in the Kassena-Nankana district between January 1 and December 31, 2004 were eligible for the study. Three thousand four hundred and thirty three women completed interviews on socio-demographic and pregnancy related factors. Information on 259 communities including travel distance to the nearest health facility was also obtained. Multilevel logistic regression analyses were conducted. RESULTS: ninety eight percent of women received antenatal care but only 38% delivered with the assistance of health professionals. In a multilevel logistic model, physical access factors {such as availability of public transport, odds ratio (OR) = 1.50 (1.15-1.94), travel distance to the district hospital [for 20+ km, OR = 0.31 (0.23-0.43)] as well as community perception of access to the nearest health facility [for highest quintile, OR = 4.44 (2.88-6.84)]} showed statistically significant associations with use of health professionals at last delivery. Women who knew that delivery care was free of charge were 4.6 times more likely to use health professionals. Higher parity was strongly negatively associated with use of health professionals [OR = 0.37 (0.29-0.48) for parity > or = 4 compared to parity 0-1]. However, community perception of quality of care was not associated with use of health professionals for delivery. CONCLUSION: Physical access factors remain strong determinants of use of professional delivery care in rural northern Ghana.